Clinical features of brain activation deficit in children (2017)
Introduction: Brain activation is considered as one of the mechanisms of the brain related to the functional state of deep subcortical structures. A deficit in this mechanism may be involved in behavioral disorders during development and school learning.Objective: To identify the clinical features of Mexican schoolchildren with general brain activation deficit, and to determine the neuropsychological tasks that help to detect this syndrome.Materials and methods: The sample included 20 Mexican schoolchildren attending regular schools and diagnosed with behavioral and/or learning disorders. The types of errors and performance in neuropsychological tasks were analyzed by categories.Results: The results showed that there are common clinical features in schoolchildren, particularly, executive instability, fatigue and/or slow execution, and instability in memory and perceptive graphic tasks. These features can be demonstrated through the qualitative syndromic analysis of perceptive graphic tasks, retention tasks and manual praxis.Conclusions: Qualitative assessment is effective to differentiate this type of cases from other possible neuropsychological conditions.